Giant uterine leiomyoma in a young woman as an incidental finding after a car accident: a case report - Bartoš, Vladimír; Korec, Peter; Ficek, Róbert (Acta Medica, 2018)
Leiomyomas are the most common benign tumor of the uterus. Occasionally, they may reach an extreme dimension. The authors present a case of a 44-year old woman, who suffered a car accident as a driver of personal motor vehicle. At the hospital, a huge tumor mass filling the entire abdominopelvic cavity was incidentally detected. The patient admitted a progressive abdominal enlargement for the last 5 years. An urgent laparotomy was performed, during which a giant, well-demarcated tumor arising from the uterine body had been disclosed. It was completely surgically removed and sent for histopathology. Grossly, the tumor measured 30 × 30 × 20 cm in the largest diameters and weighed 8.1 kg. The tissue was markedly edematous with foci of massive hemorrhages and contained confluent pseudocystic formations of various sizes, filled with a fluid and fresh blood. Solid foci of rubber consistency were also visible. Microscopic examination revealed a conventional subserous uterine leiomyoma with marked regressive and degenerative changes. Giant uterine leiomyomas occur extremely rare, but because of the often unexpected finding and atypical presentation, they may represent a great diagnostic challenge for both, pathologists and clinicians. At the biopsy examination, a multiple-section sampling is very important to avoid the possibility of underlying malignancy.
Keywords: Liver; Lung Injury; dospělí; poškození plic; tumor burden; Female; zhmoždění; Lung; játra; Adult; ženské pohlaví; Tomography, X-Ray Computed; Accidents, Traffic; lidé; Tumor Burden; Uterine Neoplasms; Rib Fractures; hemoperitoneum; sternum; Humans; nádory dělohy; Leiomyoma; Sternum; fraktury žeber; plíce; Hemoperitoneum; Contusions; Incidental Findings; leiomyom; náhodný nález; dopravní nehody; počítačová rentgenová tomografie